Kerja Sama Pertahanan Indonesia: Strategi Penguatan Keamanan Regional Asean Dalam Menghadapi Ancaman Di Asean - Imam Budiman; Bulbul Abdurachman; Naila Essenza Quraniq; Talitha Sani Azmi; Fahira Yuki Aulia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2026)
This research is part of the Higher Education Leading Basic Research Program (Penelitian Dasar Unggulan Perguruan Tinggi/PDUPT) entitled “Indonesia’s Defense Cooperation: A Strategy for Strengthening ASEAN Regional Security in Addressing Regional Threats.” The study examines how Indonesia develops defense cooperation as a strategic response to the evolving security dynamics in the Indo-Pacific, particularly amid intensifying major power rivalry reflected in the escalation of the South China Sea dispute and the establishment of AUKUS. The research pursues three main objectives: (1) to map Indonesia’s and ASEAN’s threat perceptions using the Balance of Threat framework; (2) to analyze Indonesia’s defense cooperation patterns through bilateral, multilateral, and minilateral arrangements within the Regional Security Complex framework, particularly the Regional Security Architecture; and(3) to examine the role of Indonesian diplomacy in managing security threats across ASEAN. This study employs a descriptive qualitative approach, utilizing literature review, policy document analysis, and secondary data obtained from relevant institutions. Data were analyzed systematically through data reduction, categorization, and conclusion drawing based on regional security conceptual frameworks. The findings indicate that threat perceptions are dynamic and shaped by the interaction of the four variables of the Balance of Threat theory. Indonesia responds by diversifying defense partnerships across bilateral, multilateral, and minilateral levels, strengthening military capabilities through the Minimum Essential Force (MEF) modernization program, and employing diplomacy as a key instrument for managing identified regional security threats. This research has reached Technology Readiness Level (TRL) 3, with the mandatory output being publication in a nationally accredited scientific journal.